Assessment of urban stream sediment pollutants entering estuaries using chemical analysis and multiple bioassays to characterise biological activities - Böhler, Svenja; Strecker, Ruben; Heinrich, Patrick; Braunbeck, Thomas (The science of the total environment, 2017)
Stormwater contaminants are a major source of often neglected environmental stressors because of the emphasis placed on the management of municipal and industrial wastewaters. Stormwater-derived pollutants in sediments from two New Zealand estuaries was characterised by analytical chemistry and bioassays. Contaminants were extracted from sediment using accelerated solvent extraction (ASE), recovered and concentrated by solid phase extraction (SPE), and analysed for polycyclic aromatic hydrocarbons (PAHs), selected metals, and musk fragrances. The concentrations of PAHs were below the ANZECC Interim Sediment Quality Guideline values while those of lead and zinc exceeded them in some samples. The sediment extracts containing organic contaminants exhibited acute toxicity in the zebrafish fish embryo toxicity (FET) and teratogenicity, induction of biotransformation (EROD activity), and genotoxicity (comet assay) in zebrafish. The potential of the extracts to interact with endocrine signalling processes was assessed by GeneBLAzer reporter gene bioassays and they exhibited estrogenic, androgenic, and anti-progestagenic activities.